2023
DOI: 10.1111/all.15621
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of platelets in severe allergy by an integrative omics approach

Abstract: Background: Mechanisms causing the onset and perpetuation of inflammation in severe allergic patients remain unknown. Our previous studies suggested that severe allergic inflammation is linked to platelet dysfunction. Methods:Platelet-rich plasma (PRP) and platelet-poor plasma (PPP) samples were obtained by platelet-apheresis from severe (n = 7) and mild (n = 10) allergic patients and nonallergic subjects (n = 9) to perform platelet lipidomics by liquid chromatography coupled to mass spectrometry (LC-MS) and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 46 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…Whole blood hemograms showed no differences in platelet and white blood cell counts between the experimental groups. As we have previously shown [ 10 ], platelet-rich plasma (PRP) hemograms confirmed the absence of other blood cell types, which ensured the purity of the PL-EV samples. Likewise, platelet counts and mean platelet volume did not differ between experimental groups ( p > 0.05, Table S2 ).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Whole blood hemograms showed no differences in platelet and white blood cell counts between the experimental groups. As we have previously shown [ 10 ], platelet-rich plasma (PRP) hemograms confirmed the absence of other blood cell types, which ensured the purity of the PL-EV samples. Likewise, platelet counts and mean platelet volume did not differ between experimental groups ( p > 0.05, Table S2 ).…”
Section: Resultssupporting
confidence: 60%
“…Recent studies have highlighted platelet alterations in inflammatory conditions such as rheumatoid arthritis [ 5 ], multiple sclerosis [ 6 ], Crohn’s disease [ 7 ], sepsis [ 8 ], and, more recently, allergy [ 9 , 10 ]. In fact, we have previously found that platelets from severely allergic patients present a specific lipid content that could contribute to the development of chronic inflammation [ 10 ]. In these inflammatory disorders, platelets become activated and release their content together with extracellular vesicles (EVs) [ 11 , 12 ], which could alter platelet–immune cell communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding, together with the alterations observed in FAO, point to an altered regulatory function in severe allergic asthmatic patients. In fact, the lack of regulation capacity might be a key mechanism in the maintenance of the inflammatory state in these patients ( 1 , 7 , 24 ). We have already demonstrated that severe respiratory allergic patients presented an enhanced inflammatory immune response in the oral mucosa, with an increased number of CD4 + infiltrates ( 24 ) and enhanced recruitment of Treg cells ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that severe respiratory allergic patients have specific platelet content, reduced protein synthesis, and switch of immune cells' metabolism to aerobic glycolysis ( 6 , 7 ). It has been widely described how systemic metabolism reprograms the fate of immune cells, by influencing their activation, proliferative capacity and their quiescent state in tissues and in the systemic circulation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%